Working in the Eye of the Pandemic: Local COVID-19 Infections and Daily Employee Engagement - Reinwald, Max; Zimmermann, Sophia; Kunze, Florian (Frontiers in Psychology, 2021)
The COVID-19 pandemic has drastically changed many aspects of our society and work life. This study assesses how daily variations in employees’ work engagement are affected by daily variations in infection rates in employees’ communities. Applying the conceptual framework of event system theory, we argue that surging COVID-19 cases have an impact on employee engagement, depending on the individual sensemaking processes of the pandemic. We assume that employee age and received leader support are key context factors for these sensemaking processes and that particularly older employees and employees who receive little leader consideration react with lower work engagement levels toward rising local COVID-19 infections in their proximity. We find support for most of our proposed relationships in an eight-day diary study of German employees, which we integrate with official COVID-19 case statistics on the county level. We discuss the implications of these results for the literature on extreme events and individual workplace behavior. Furthermore, these findings have important implications for companies and executives who are confronted with local COVID-19 outbreaks or other extreme societal events.